2023
DOI: 10.1021/acsaem.2c03216
|View full text |Cite
|
Sign up to set email alerts
|

Electron Probe Bridging Solid-State Chemistry and Surface Chemistry: Example of the TiO2-O2 System

Abstract: This work reports the capacity of a high-temperature electron probe to bridge solid-state chemistry and surface chemistry. This goal could be accomplished by performing the characterization of the surface layer in equilibrium with both the gas phase and bulk phase, thus dealing with a system governed by thermodynamic laws, which is free of unknown kinetic terms. In this work, we contemplate the use of the electron probe in surface defect engineering of the next generation of energy materials, that are expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…The related charge neutrality condition requires that the charge of chemisorbed (molecular and atomic) oxygen species is compensated by the space charge within the boundary layer. At elevated temperatures, chemisorbed oxygen species are quickly incorporated into the surface layer in the form of doubly ionized oxygen ions, 7,15 then these species migrate through the electric fields within the space charge layer. It has been shown that these fields have a substantial impact on surface segregation of defects, which is rate controlled by diffusion.…”
Section: Reactivity Mechanismmentioning
confidence: 99%
See 4 more Smart Citations
“…The related charge neutrality condition requires that the charge of chemisorbed (molecular and atomic) oxygen species is compensated by the space charge within the boundary layer. At elevated temperatures, chemisorbed oxygen species are quickly incorporated into the surface layer in the form of doubly ionized oxygen ions, 7,15 then these species migrate through the electric fields within the space charge layer. It has been shown that these fields have a substantial impact on surface segregation of defects, which is rate controlled by diffusion.…”
Section: Reactivity Mechanismmentioning
confidence: 99%
“…The prolonged drift of WF changes suggests the progression of a slow surface reaction that is associated with segregation of defects, as it has been observed during prolonged annealing of TiO 2 . 15 The full gas/solid equilibrium in the Fe 2 O 3 -O 2 system is established after 300 h at 1140 K.…”
Section: Surface Equilibration Mechanismmentioning
confidence: 99%
See 3 more Smart Citations